Effective Growing Degree Days as a Critical Factor for Yield and Qualitative Values of Timothy in Subarctic Growing Conditions - Nissinen, Oiva (UKnowledge, 2021)
The yield and forage quality of timothy (Phleum pratense L.) leys at different stages of development were studied in 1991-1999 at the Lapland Research Station of the Agricultural Research Centre of Finland in Rovaniemi (66o35´N). The aim of the study was to determine the optimal time for the first cut with respect to yield and qualitative values. In timothy the first heads were visible on 25 June on average and full heading was seen on 5 July, i.e. some ten days later. During this period the dry matter yield increased from 2769 to 4945 kg/ha, crude protein content decreased from 16.6 to 11.7%, crude fibre increased from 27.1 to 33.9% and organic matter digestibility decreased from 74.4 to 65.1% in dry matter. There was, however, a significant (P < 0.05) correlation between effective growing degree days (GDD, base +5oC) and growth rate, dry matter yield, crude fibre content and organic matter digestibility at the very beginning of heading. Effective GDD lower than 280oC delayed the heading of timothy by 7 days but increased the dry matter yield by 27% compared to effective GDD higher than 280oC. Simultaneously, higher temperature accumulation decreased the crude protein content by 0.6 percentage points, increased crude fiber by 2.3 percentage points and decreased organic matter digestibility by 2.3 percentage points in dry matter.